Testing a new light therapy for the treatment of actinic keratosis. (2nd January 2020) - Mordon, S.; Vignion‐Dewalle, A.S.; Abi‐Rached, H.; Thecua, E.; Lecomte, F.; Vicentini, C.; Deleporte, P.; Béhal, H.; Kerob, D.; Hommel, T.; Duhamel, A.; Szeimies, R.M.; et al.
Summary: An actinic keratosis (AK) is an area (lesion) of sun‐damaged skin, mainly found on sun‐exposed parts of the body, particularly the forearms, backs of the hands, face, ears, bald scalp and the lower legs. Left untreated, there is a small risk that an AK could progress into a form of skin cancer called squamous cell carcinoma. One way of treating AK is called photodynamic therapy (PDT). The usual, or conventional, protocol for using PDT to treat AK is called C‐PDT. It involves applying a light‐sensitising cream to the skin which is activated by a high‐intensity red light about 2.5 hours later. This causes intense inflammation in the skin which destroys abnormal, but not normal, skin tissue. The main drawback of C‐PDT is the pain experienced by patients during the treatment. Due to this pain, many patients cannot complete the treatment. The authors of this study, based in France and Germany, proposed a new protocol for PDT of AK, called P‐PDT. P‐PDT involves a revised red light activation: the light intensity has been considerably reduced and the activation begins only 30 minutes after the molecule (cream) application. This revision was expected to increase the patient's tolerance. The primary aim of the study was to assess whether P‐PDT is at least as effective as C‐PDT in destroying AK. One of the secondary aims was to compare pain levels between P‐PDT and C‐PDT. Forty‐six patients with AKs of the head were included. These patients were treated with P‐PDT on one side of the head and with C‐PDT on the other side. With 94.2% disappearance of AKs six months after the treatment, P‐PDT was found to be at least as effective as C‐PDT, which had a disappearance rate of 94.9%. Moreover, from the pain levels reported by the patients for each protocol, P‐PDT is much less painful, or even painless, compared to C‐PDT. This summary relates to the study: The conventional protocol vs. a protocol including illumination with a fabric‐based biophotonic device (the Phosistos protocol) in photodynamic therapy for actinic keratosis: a randomized, controlled, noninferiority clinical study Abstract : Linked Article: Mordon et al. Br J Dermatol 2020; 182 :76–84